Три поросёнка - Михалков Сергей Владимирович (Серия "Самовар" – малышам", 2003)
Экземпляры: М/а ДБ (20210804) / Инвентарный номер: 114755 / Цена: 20.00 / Авт.знак: М 69 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6